A word of caution using self‐expanding transcatheter aortic valve‐frame infolding. Issue 3 (30th October 2018) - Ben‐Dor, Itsik; Rogers, Toby; Satler, Lowell F.; Waksman, Ron
Abstract: Transcatheter aortic valve replacement has become a mainstay alternative to surgical aortic valve replacement in patients with severe aortic stenosis at high and intermediate surgical risk. Two commercially approved valves are available in the United States: balloon‐expandable and self‐expanding. We report here a rare complication of a self‐expanding Evolut PRO (Medtronic, Minneapolis, Minnesota) valve failing to expand due to nitinol frame infolding. This results in a malopposed valve with a severe paravalvular leak, even though treated successfully with balloon valvuloplasty. It is important to recognize the characteristic angiographic signature of this complication—the "straight line" sign—and how to avoid this potentially serious complication by balloon valvuloplasty or by recapture and deployment of a new valve.